Compressive Behavior and Analytical Model of Ultra-Early Strength Concrete-Filled FRP Tube With Zero Curing Time - Liu, Yue; Xie, Jia-Zhan; Yan, Jing-Liang (Frontiers in Materials, 2022)
Fibre Reinforced Polymer (FRP) has been widely used in civil engineering due to its light weight, high strength, convenient construction and strong corrosion resistance. One of the important applications of FRP composites is the concrete filled FRP tube (CFFT), which can greatly improve the compressive strength and ductility of the concrete as well as facilitate construction. In this paper, the compressive performances of normal concrete filled FRP tube (N-CFFT) column with five hours curing time and ultra-early strength concrete filled FRP tube (UES-CFFT) column with zero curing time were studied by considering the characteristics of rapid early strength improvement of ultra-early strength concrete and the confinement effect of FRP tube. Monotonic axial compression tests were carried out on 3 empty FRP tubes (FT) without internal filler and 6 CFFT (3 N-CFFT and 3 UES-CFFT) specimens. All specimens were cylinders of 200 mm in diameter and 600 mm in height, confined by glass fibre reinforced polymer (GFRP). Test results indicated that the compressive bearing capacity of the specimens increased significantly by adopting the ultra-early strength concrete as the core concrete of the CFFT, although the curing time was zero. It was also shown that the compressive behavior of the UES-CFFT specimens with zero curing time increased significantly than that of the N-CFFT specimens with five hours curing time because the former was ability to achieve rapid strength enhancement in a very short time than the latter. The ultimate compressive strength of UES-CFFT specimens with zero curing time reached 78.3MPa, which was 66.2 % and 97.2 % higher than that of N-CFFT with five hours curing time and FT specimens, respectively. In addition, a simple confinement model to predict the strength response of UES-CFFT specimens with zero curing time in ultimate condition was introduced. . Compared with the existing models, the proposed model could predict the ultimate strength response of UES-CFFT specimens with zero curing time with better accuracy.